THE EFFECT OF RATION CONTAIN OF FERMENTED SKIN DRAGON FRUIT (Hylocereus Undatus) WITH YEAST Saccharomyces cerevisiae ON PERFORMANCE OF KAMPUNGCHICKEN AGE 2-8 WEEKS - I K., Okstrada; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
A study aimed to determine performance of kampong chicken age 2 – 8 weeks given ration containing dragon skin fruit meal fermented Saccharomyces cerevisiae with level 5%, 7%, and 9%. The Study was conducted at research station Faculty of Animal Science, Udayana University Jimbaran, Badung, Bali for 2 month. The study used Randomized complete design (RCD) with 4 treatmens and 5 replicated. Those treatments as follows RKBN0 : Rations without fermented of skin dragon fruits and whereas RKBN1, RKBN2, and  RKBN3 contained 5%, 7% and 9% fermented of skin dragon fruit respectively. Variables observed were final weight, weight gain, feed consumption and feed conversion ratio/FCR. Result showed that fed ration containing dragon skin fruit meal fermented Saccharomyces cerevisiae with level 7% (RKBN2) and 9% (RKBN3) decrease (P<0,05) feed consumtion ration were 4,41% and 7,45% respectively, but no effect for final body weight, weight gain, and FCR of kampong chicken age 2 – 8 weeks. Key words: K amp u ng chicken, S kin of  dragon fruit, Performance, Saccharomyces cerevisiae.